Allergic Contact Dermatitis Due to Daily Soap Products: A Case Report - Sugih Primas Adjie; Harijono Kariosentono (Journal of Social Research, 2025)
Allergic contact dermatitis (ACD) is a skin disorder that results from contact with an allergenic substance. Allergic contact dermatitis is most commonly caused by cosmetics and daily products. This case report describes a case of contact dermatitis caused by soap suspected of containing sodium lauryl sulfate (SLS) and fragrance with a positive patch test result. A 36-year-old man presented with complaints of hand skin redness, itching and scaling. A history of using dish and hand soap products was obtained. Dermatologic examination showed multiple erythematous patches with overlying squamous, xerotic skin suggestive of DKA. The patient underwent patch test examination with standardized materials and materials brought by the patient to confirm the diagnosis. The patient showed positive reactions to Sunlight® dishwashing liquid soap, Super pell® mop soap, wow® dish soap, calmic® hand soap, and so iln® liquid detergent. The diagnosis of BCC can be established based on anamnesis, physical, and anatomical histopathological examination. Diagnosis of BCC is accomplished by accurate interpretation of the skin biopsy results. Histopathological examination should be performed in cases of doubtful lesions, large tumors or ulcerations for which the diagnosis is uncertain and to assess surgical margins. Therapy for BCC is preventive and curative. Therapy selection depends on the patient's age and gender as well as the site, size, and type of lesion.